Aspects of treatment of patients with abdominal oncopathology against the background of chronic kidney disease - I. A. Paltyshev; M. A. Belyaev; A. A. Zakharenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2025)
Onconephrology is a branch of medical science located at the junction of specialties (oncology and nephrology), which deals with aspects of kidney diseases that have arisen against the background of cancer treatment, as well as the course of the oncological process against the background of previously identified chronic kidney disease (CKD). The literature review highlights some problems related to the treatment of cancer patients with kidney dysfunction: epidemiology, features of diagnostic and dynamic examinations, surgical and chemotherapeutic treatment, as well as a number of organizational problems that arise when planning treatment for this complex group.